Metodologi Tafsir Kontemporer dalam Buku Major Themes of the Quran Karya Fazlur Rahman - Abdurrohim (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2020)
As the leading guide of Muslims in life and life, the Quran is always interesting to study, a lot of efforts of the scholars to interpret the contents of the holy verses in it. Fazlur Rahman is one of the many contemporary scholars who have the idea of a unique approach, and maybe it could be new in the world of interpretation. One approach in understanding the Koran, he poured in the book "Major Themes of the Quran" which is until now has been used as reference, especially in interpretation's methodology of the Quran.  From the results of an in-depth study, an explanation of Fazlur Rahman's approach obtained to interpret the Quran verses. It is called Synthesis-Logical, socio-historical, with a dual movement hermeneutic approach. Furthermore, in "Major Themes of the Quran" Fazlur Rahman uses the Synthesis-Logical method. On the other hand, the idea of the Synthesis-Logical Method when examined further turns out to have similar classical interpretation approach, called Maudhu'? with munasabah approach.  Keywords: Fazlur Rahman, contemporary interpretation, methods.